A Two-Eyed Seeing Context-based Approach for Incorporating Indigenous Knowledge into School Science Teaching. Issue 2 (3rd May 2020) - Onwu, Gilbert O. M.; Mufundirwa, Charles
Abstract : This paper is about using a 'Two-Eyed Seeing' approach as the process of co-learning for incorporating elements of indigenous knowledge into school science teaching. Two groups of 150 Form 3 integrated science learners drawn from six high schools in Mutare, Zimbabwe, comprised the study sample. One group of learners, the control group, was taught the concepts of forces in structures in the traditional way. The other, the experimental group, was prepared using a context-based Two-Eyed Seeing framework. A mixed-method but primarily quantitative research approach involving a pre-test–post-test control group quasi-experimental design was used to investigate the achievement differences between the two groups of learners. A content knowledge test (CKT) and a paper-and-pencil theory of practical skills test (PST) were administered to the two groups prior to and following instruction. The analysis showed that the experimental group produced significantly better results than the group following the traditional approach (CKT, F  = 131.593, p  < 0.0001; PST, F  = 116.350, p  < 0.0001). Focus group interviews indicated that achievement differences were strongly linked to the pairing of indigenous knowledge and technology as relevant pedagogical contexts with the school science content knowledge, which resulted in intrinsic motivation for meaningful learning. The qualitative data complemented the quantitative data.